1991
DOI: 10.1177/030006059101900313
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Insomnia with Zolpidem: A Multicentre General Practitioner Study of 107 Patients

Abstract: The effects of zolpidem, an imidazopyridine derivative, were studied in 107 patients suffering from insomnia, 60.9% of whom were over 60 years of age, in a 6-month, single-blind, flexible dose, general practitioner study. Comparison was made between baseline, last day of treatment and 10 days after the end of treatment to assess efficacy and rebound insomnia. An improvement in all efficacy parameters--time taken to fall asleep, total amount of nocturnal sleep and number of nocturnal awakenings--was reported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…A single-blind trial published in 1991 reported on the nightly use of zolpidem for up to 6 months; the authors concluded that 10 mg/d is an appropriate starting dose and is effective and safe for the treatment of sleep disturbances of various origins. 5 Generally, because of zolpideminduced amnesia for sleep disturbances, this popular drug is thought to produce a patient's subjectively better quality of sleep without the evident adverse effects that usually accompany hypnotics. The risk of abuse and tolerance is low when zolpidem is used as directed.…”
mentioning
confidence: 99%
“…A single-blind trial published in 1991 reported on the nightly use of zolpidem for up to 6 months; the authors concluded that 10 mg/d is an appropriate starting dose and is effective and safe for the treatment of sleep disturbances of various origins. 5 Generally, because of zolpideminduced amnesia for sleep disturbances, this popular drug is thought to produce a patient's subjectively better quality of sleep without the evident adverse effects that usually accompany hypnotics. The risk of abuse and tolerance is low when zolpidem is used as directed.…”
mentioning
confidence: 99%
“…Similar comparisons and the volume of adequately reported data necessary for pooling limited the amount of analysis that could be conducted with these data. CBT-I = cognitive behavioral therapy for insomnia; CI = confidence interval; ISI = Insomnia Severity Index; k = number of studies; MD = mean difference; NR = not reported; NS = no statistical difference between groups; PSQI = Pittsburgh Sleep Quality Index; RR = risk ratio; SC = stimulus control; SMD = standardized mean difference; SOE = strength of evidence; WMD = weighted mean difference (113). Low Insufficient Insufficient Insufficient Insufficient AIS = Athens Insomnia Scale; BBT = brief behavioral therapy; CBT-I = cognitive behavioral therapy for insomnia; CI = confidence interval; ISI = Insomnia Severity Index; k = number of studies; MBT = multicomponent behavioral therapies; MD = mean difference; NR = not reported; NS = no statistical difference between groups; PSQI = Pittsburgh Sleep Quality Index; SC = stimulus control; SMD = standardized mean difference; SOE = strength of evidence; WMD = weighted mean difference CBT-I = cognitive behavioral therapy for insomnia; CI = confidence interval; ISI = Insomnia Severity Index; k = number of studies; NR = not reported; SMD = standardized mean difference; SOE = strength of evidence; WMD = weighted mean difference…”
Section: Efficacy Comparative Effectiveness and Adverse Effects Of mentioning
confidence: 99%
“…60,[111][112][113][114][115] Treatment duration was between 4 and 6 weeks for five of the trials. One trial was longer-term, with treatment duration up to 8 months.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations